2007
DOI: 10.1159/000101051
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Synthetic SAG1 (p30) Peptide Sequences with RH, S273 and Beverley Strain-Induced Anti-<i>Toxoplasma gondii</i> Antibodies

Abstract: Objectives: We compared the reactivity of IgG1 and IgG2a antibodies in mouse sera after infection with virulent RH and low-virulent S273 and Beverley strains of Toxoplasma gondii against RH SAG1 recombinant p30 (rp30) and synthetic SAG1 peptides. Methods: Infected mouse serum samples were collected 9 days after infection, and the level of total IgG, IgG1 and IgG2a against the RH SAG1 rp30 protein and twenty peptides of the RH SAG1 protein were assessed. The glycosylphosphatidylinositol (GPI) modification site,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
4
6
0
Order By: Relevance
“…In the initial evaluation of the different peptide combinations by the assay, we observed that when SAG-1 was present, as in the MAP1, the sensitivity and specificity in the detection of IgG, IgM and IgA antibodies in different toxoplasmosis phases was higher compared with those without SAG-1, as MAP4 (Table 1). Our results are consistent with the results of other investigators who have found that SAG-1 improves the sensitivity and specificity of serological assays 19,25 . In the study of other peptide combinations such as, MAP2, 3 and 4, the assay presented low diagnostic performance, and the acute/recent, non-acute/recent and chronic phase could not be distinguished as in the assay using MAP1.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the initial evaluation of the different peptide combinations by the assay, we observed that when SAG-1 was present, as in the MAP1, the sensitivity and specificity in the detection of IgG, IgM and IgA antibodies in different toxoplasmosis phases was higher compared with those without SAG-1, as MAP4 (Table 1). Our results are consistent with the results of other investigators who have found that SAG-1 improves the sensitivity and specificity of serological assays 19,25 . In the study of other peptide combinations such as, MAP2, 3 and 4, the assay presented low diagnostic performance, and the acute/recent, non-acute/recent and chronic phase could not be distinguished as in the assay using MAP1.…”
Section: Discussionsupporting
confidence: 93%
“…However, current laboratory practice using highly sensitive automated equipment has led to problems with the detection of parasite specific IgG and IgM antibodies 12,33 . Several authors have shown that IgM to T. gondii can be detected for a long period after the primary infection and false positivities with IgG to T. gondii have been reported which are non-significant and erroneously interpreted as positive results indicating acute infection and protection 19 . Research and development have continued to advance and new parameters have been developed for the diagnosis of toxoplasmosis in its different phases, such as the avidity test of IgG antibodies and detection of the parasite by a molecular method such as polymerase chain reaction (PCR).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several experimental approaches have been used to identify protein regions and epitopes suitable for the serological diagnosis of T. gondii, including phage display of cDNA libraries, epitope mapping, and reactivity with monoclonal antibodies (5,11,26,29,41,49). For this study, a bioinformatic approach was used for in silico prediction of 20 B-cell linear epitopes on the T. gondii antigenic proteins GRA1, GRA2, GRA4, and MIC3.…”
mentioning
confidence: 99%
“…For this study, a bioinformatic approach was used for in silico prediction of 20 B-cell linear epitopes on the T. gondii antigenic proteins GRA1, GRA2, GRA4, and MIC3. These 20 novel peptides and 18 peptides reported in studies previously published by others (6,11,25,26) were printed into a peptide microarray and validated by analyzing a large number of well-characterized human serum samples.…”
mentioning
confidence: 99%